Comparison of the Effectiveness of Sequential Organ Failure Assessment (SOFA) and Quick Sequential Organ Failure Assessment (qSOFA) in Predicting Mortality in Secondary Non-Traumatic Peritonitis Patients - Nurwansyah; Irfanuddin; Alsen Arlan (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2018)
Introduction. Peritonitis has a high mortality rate, SOFA is a scoring system that represents 6 organ functions namely respiration, blood coagulation, liver, cardiovascular, Central Nervous System, and Kidney the higher the SOFA score the higher the possibility of mortality, qSOFA is a new scoring , practical and has a strong predictive value. Method. This study was a diagnostic study in the form of a suitability test to assess the sensitivity, specificity, PPV and NPV, cut of points and the suitability of the SOFA and qSOFA scoring systems in predicting outcomes of patients with secondary peritonitis in RSMH Palembang. Results. Data processing was performed on 27 study subjects during November 2017-June 2018. SOFA prognosis test results with a cut-off point >5 obtained a sensitivity of 84.2%, 100% specificity, PPV 73.68%, NPV 100%, prognosis test results qSOFA with a cut off point> 2 Obtained a sensitivity of 91.7%, specificity of 100%, PPV 91.66%, NPV 80%, Conclusion.The qSOFA scoring system was more efficient than SOFA in predicting mortality